DIGITAL PLATFORM-BASED GAMIFICATION: DEVELOPMENT OF LEARNING MEDIA TO SUPPORT THE ENGAGEMENT AND MOTIVATION OF HIGH SCHOOL STUDENTS - Nuraida, Nining (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research aims to develop gamified learning media based on digital platforms to support student engagement and motivation in Islamic Religious Education subjects at SMK N 4 Jambi City. The development model used is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Media validation was conducted by media experts, content experts, teachers, and students using a five-point Likert scale-based validation questionnaire. The validation results showed that the media was declared highly feasible, with an average validation score percentage of 88% for media experts, 85% for content experts, and teacher and student responses falling into the very good category, indicating the technical, content, and practical feasibility of the media for use in learning. Limited trials also revealed that this medium is capable of increasing student engagement and learning motivation, with engagement percentages reaching 78.4% and learning motivation increasing compared to conventional teaching methods. Thus, the gamified learning media based on a digital platform developed is suitable for use as an innovative alternative to support increased student engagement and learning motivation in vocational high schools.